Pentacoordinated Al3+‐Stabilized Active Pd Structures on Al2O3‐Coated Palladium Catalysts for Methane Combustion. (24th July 2019) - Duan, Huimei; You, Rui; Xu, Shutao; Li, Zhaorui; Qian, Kun; Cao, Tian; Huang, Weixin; Bao, Xinhe
Abstract: Supported Pd catalysts are active in catalyzing the highly exothermic methane combustion reaction but tend to be deactivated owing to local hyperthermal environments. Herein we report an effective approach to stabilize Pd/SiO2 catalysts with porous Al2 O3 overlayers coated by atomic layer deposition (ALD). 27 Al magic angle spinning NMR analysis showed that Al2 O3 overlayers on Pd particles coated by the ALD method are rich in pentacoordinated Al 3+ sites capable of strongly interacting with adjacent surface PdO x phases on supported Pd particles. Consequently, Al2 O3 ‐decorated Pd/SiO2 catalysts exhibit active and stable PdO x and Pd–PdO x structures to efficiently catalyze methane combustion between 200 and 850 °C. These results reveal the unique structural characteristics of Al2 O3 overlayers on metal surfaces coated by the ALD method and provide a practical strategy to explore stable and efficient supported Pd catalysts for methane combustion. Abstract : Aktiv bleiben : Al2 O3 ‐Schichten auf Pd‐Partikeln sind reich an pentakoordinierten Al 3+ ‐Stellen, denen es möglich ist, stark mit benachbarten Oberflächen‐PdO x ‐Phasen auf trägerfixierten Pd‐Partikeln zu wechselwirken. Die resultierenden aktiven und stabilen PdO x ‐ und Pd‐PdO x ‐Strukturen katalysierten die Methanverbrennung effizient zwischen 200 und 850 °C (siehe Bild; o‐Pd/SiO2 ‐T bezeichnet den Trägerkatalysator, der Pd‐Oktaeder auf SiO2 ‐Nanokugeln umfasst).